MEMBANGUN KEBERSAMAAN UMAT HINDU KABUPATEN BLITAR - Sujaelanto (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2025)
Religion is not only a guide for each person's personal life but also serves as a social glue for socio-religious life in society. However, in reality, religion also contributes to conflict and division when its teachings are interpreted in an incomprehensible manner. In today's world, the wealthy, who should be helping, instead expect to be helped. The Hindu concept of